Knowledge and awareness on vector-borne diseases: a pending subject for the Spanish society? - Gonzálvez, Moisés; Asensio, María Del Mar; Muñoz-Hernández, Clara; Ruiz de Ybáñez, Rocío (Anales del sistema sanitario de Navarra, 2024)
To evaluate the level of knowledge and risk perception regarding vector-borne diseases in the Spanish society and identify the risk factors associated with the level of understanding. An online survey was conducted between January and May 2021, targeting Spanish adults. The survey consisted of 11 questions assessing knowledge and risk perception related to vector-borne diseases. Sociodemographic variables predicting the outcome variable (objective level of knowledge, determined by correctly naming two vector-borne diseases) were analyzed using multiple logistic regression. The outcome variable was then compared with the self-reported knowledge declared by the participants (kappa coefficient),k. Out of the 1,646 respondents who completed the survey, 72.2% were female and 59.8% were >40 years old). Additionally, 87.3% showed a high risk perception and 61.7% understood what is a vector; however, only 36.3% had an objective level of knowledge (k= 0.353). The variables being >40 years (p <0.0001), having a monthly income >1,500 € (p <0.0001), and owning pets (p= 0.0423) were positively related with an objective level of knowledge on vector-borne diseases (adjusted effects). Both knowledge and perception of the risk on vector-borne diseases need to be strengthened in Spain, especially in regions where vector-borne diseases are endemic, emerging, or re-emerging. These preliminary results underscore the necessity of enhancing institutional efforts to build a robust knowledge base within the Spanish society, extending beyond scientific forums.